1993
DOI: 10.1093/clinids/17.supplement_1.s79
|View full text |Cite
|
Sign up to set email alerts
|

Serological Diagnosis of Mycoplasma pneumoniae Infections: A Critical Review of Current Procedures

Abstract: Respiratory diseases due to Mycoplasma pneumoniae are still confirmed with serological methods, although during the acute phase of M. pneumoniae disease indicative parameters are frequently negative. This result is true not only for serodiagnosis based on tests for the presence of cold hemagglutinin (the first but unspecific acute-phase parameter; these are positive in only about 50% of cases) but also for serodiagnosis based on CF tests, particle agglutination tests, or even enzyme-linked immunoassays that te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0
10

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(109 citation statements)
references
References 24 publications
2
97
0
10
Order By: Relevance
“…10 11 DiVerentiation between M pneumoniae and M genitalium, both of which can be isolated from respiratory samples, is not easy, 12 13 and the culture of C psittaci could be hazardous. 14 Frequently, insensitive and cross reacting serological techniques, [15][16][17] such as the complement fixation test, are being used as the main diagnostic test. As a result of these factors, and also of the timing of the research, conflicting prevalences of these atypical infections have been reported, ranging from 1% to 40%.…”
Section: -3mentioning
confidence: 99%
“…10 11 DiVerentiation between M pneumoniae and M genitalium, both of which can be isolated from respiratory samples, is not easy, 12 13 and the culture of C psittaci could be hazardous. 14 Frequently, insensitive and cross reacting serological techniques, [15][16][17] such as the complement fixation test, are being used as the main diagnostic test. As a result of these factors, and also of the timing of the research, conflicting prevalences of these atypical infections have been reported, ranging from 1% to 40%.…”
Section: -3mentioning
confidence: 99%
“…There was no chest pain or dyspnea reported. The initial complete blood count revealed a white cell count of 16.8×10 worldwide; its sensitivity and specificity is 90% and 94%, respectively (16). Although the specificity of the PA test is inferior to that of the CFT, the sensitivity of it is similar to that of the CFT or ELISA (13,14,17).…”
Section: Case Reportmentioning
confidence: 96%
“…The cold agglutinins test was performed at the bedside; the results were positive, which have been associated with M pneumoniae disease in 30% to 50% of cases. 6 Given the diffi culty in quickly and accurately diagnosing M pneumoniae with serology samples alone, Mycoplasma polymerase chain reaction analysis was requested as an adjunctive test; however, this test was not available at our laboratory.…”
Section: Question: Does This Patient Have M Pneumoniae -Associated Mumentioning
confidence: 99%